(untitled) (Bangladesh Journal of Medical Science, 2026)
Background Stroke is the second leading cause of death and the third leading cause of disability worldwide. Early damage of the blood-brain barrier after ischemic stroke leads to progressive neuronal death and brain edema. Tight junctions between endothelial cells, including occludins and claudins, are critical for BBB integrity, and their disruption contributes to stroke pathology. Objective To evaluate serum levels of occludin and claudin-5 in patients with acute ischemic stroke and their association with stroke severity, functional outcomes, and vascular risk factors. Methods This prospective study included 88 patients with acute ischemic stroke or transient ischemic attack. Baseline clinical characteristics, including NIHSS and modified Rankin Scale (mRS) scores, were assessed. Serum occludin and claudin-5 levels were measured on day one of admission. Patients were stratified by stroke severity (NIHSS) and outcomes (mRS), and subgroup analysis was conducted based on vascular risk factors. ROC curve analysis evaluated the predictive value of occludin and claudin-5 for mortality. Results The average NIHSS score was 10.2 ± 5.30, and the mean mRS score was 3.72 ± 0.97. Serum occludin and claudin-5 levels were 0.09 ± 0.34 ng/mL and 0.07 ± 0.44 ng/mL, respectively. No statistically significant differences were found in biomarker levels across NIHSS and mRS groups (p > 0.05), although claudin-5 showed a decreasing trend with worsening neurological and functional status.Patients with heart rhythm disturbances and diabetes mellitus exhibited slightly lower claudin-5 levels, though not significantly. ROC analysis revealed a limited discriminatory capacity of occludin (AUC = 0.525; p = 0.6845) and a moderate performance for claudin-5 (AUC = 0.614; p = 0.0884), with claudin-5 showing better sensitivity–specificity balance. Conclusion Serum occludin and claudin-5 levels did not correlate significantly with stroke severity or functional outcomes but displayed trends suggestive of their involvement in BBB disruption. Claudin-5 may hold moderate prognostic value in mortality prediction. Further large-scale studies are needed to clarify their diagnostic and prognostic potential in ischemic stroke. BJMS, Vol. 25 No. 02 April’26 Page: 615-622